Primary pulmonary diffuse large B‐cell lymphoma presenting multiple nodules mimicking metastasis: A case report. Issue 3 (22nd February 2023) - Fujioka, Nobuhiro; Kai, Yoshiro; Kataoka, Ryosuke; Suzuki, Kentaro; Sakaguchi, Kazuhiro; Yamamoto, Yoshifumi; Kawaguchi, Takeshi; Sawabata, Noriyoshi; Tanaka, Haruyuki; Matsuoka, Minami; Takeda, Maiko; Muro, Shigeo
Abstract: Primary pulmonary diffuse large B‐cell lymphoma is a rare entity. We describe a case of pulmonary lymphoma with multiple nodules mimicking metastases in a treated patient with rheumatoid arthritis. A 73‐year‐old man was diagnosed with rheumatoid arthritis at the age of 30. He was treated with leflunomide. He was followed up for a nontuberculous mycobacterial infection. He underwent percutaneous coronary intervention for acute myocardial infarction at the age of 70. In April 2022, routine follow‐up revealed new‐onset multiple nodules on chest computed tomography (CT). A position emission tomography/CT scan with 18F‐fluorodeoxyglucose showed a low‐high maximum standardized uptake value by multiple nodules. Pathologic examination of a video‐assisted thoracic surgical biopsy revealed pulmonary diffuse large B‐cell lymphoma. Systemic chemotherapy with rituximab, cyclophosphamide, vincristine, and prednisolone reduced and eliminated multiple nodules. Pulmonary lymphoma should be considered as a differential diagnosis in the case of multiple nodules on a chest CT. Abstract : Here, we report our experience with a case of primary pulmonary lymphoma‐diffuse large B‐cell lymphoma (PPL‐DLBCL) detected as multiple pulmonary nodules and masses mimicking metastasis. The cause of multiple nodules of the lung in the elderly is mostly metastasis. In our case, the images suggested metastatic lung disease; however, the final diagnosis was a PPL. Sometimes, rare malignancies may result in a better prognosis than common lung malignancies. Histological diagnosis of lung lesions is important.